2019
DOI: 10.1021/acsnano.9b08347
|View full text |Cite
|
Sign up to set email alerts
|

Weak Fragment Crystallizable (Fc) Domain Interactions Drive the Dynamic Assembly of IgG Oligomers upon Antigen Recognition

Abstract: Activation of membrane receptors through clustering is a common mechanism found in various biological systems. Spatial proximity of receptors may be transduced across the membrane to initiate signaling pathways or alternatively be recognized by peripheral proteins or immune cells to trigger external effector functions. Here we show how specific immunoglobulin G (IgG) binding induces clustering of monomeric target molecules in lipid membranes through Fc–Fc interactions. We visualize and characterize the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…Since SpA and SpA-B block the formation of IgG hexamers through the same mechanism, we focused the following experiments on SpA-B. Using a quartz crystal microbalance (QCM) that we have previously used to quantitatively study binding and oligomerization of IgG1 to antigenic supported lipid bilayers (Strasser et al, 2020), we assessed the association of wild-type IgG1 to similar DNP-SLBs as used for HS-AFM experiments and followed the subsequent binding of C1q in the presence or absence of SpA-B ( Fig 5A, B). Monitoring the resonance frequency change of the DNP-SLB-covered SiO2-coated quartz crystal, which is proportional to the change in bound mass, yields characteristic binding curves of anti-DNP IgG1-WT interacting with DNP-SLBs ( (Fig 5A), simultaneous incubation of C1q with SpA-B strongly reduced the binding signal ( Fig 5B).…”
Section: Spa Inhibits Binding Of C1q and C1 To Antigen-bound Iggs On mentioning
confidence: 99%
See 1 more Smart Citation
“…Since SpA and SpA-B block the formation of IgG hexamers through the same mechanism, we focused the following experiments on SpA-B. Using a quartz crystal microbalance (QCM) that we have previously used to quantitatively study binding and oligomerization of IgG1 to antigenic supported lipid bilayers (Strasser et al, 2020), we assessed the association of wild-type IgG1 to similar DNP-SLBs as used for HS-AFM experiments and followed the subsequent binding of C1q in the presence or absence of SpA-B ( Fig 5A, B). Monitoring the resonance frequency change of the DNP-SLB-covered SiO2-coated quartz crystal, which is proportional to the change in bound mass, yields characteristic binding curves of anti-DNP IgG1-WT interacting with DNP-SLBs ( (Fig 5A), simultaneous incubation of C1q with SpA-B strongly reduced the binding signal ( Fig 5B).…”
Section: Spa Inhibits Binding Of C1q and C1 To Antigen-bound Iggs On mentioning
confidence: 99%
“…Cryo-electron tomography and atomic force microscopy studies revealed that the six globular heads of C1q can simultaneously bind to each of the six IgG molecules that form a hexameric binding platform (Diebolder et al, 2014) (Fig EV1B). The formation of these hexamers is induced upon antibody binding to surface-bound antigens and driven by non-covalent interactions between the Fc regions of neighboring IgG molecules (Strasser et al, 2020) (Fig 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the potential of AFM for imaging Abs with near-atomistic resolution [24][25][26] and its ability for quantitatively mapping nanomechanical forces of Ab-Ag interactions at the single-molecule level [27][28][29] . Recently, high-speed (HS) AFM offers up to video-rate temporal resolution, revealing certain types of dynamic processes of IgGs, e.g., walking on the viral surface, oligomerization, and complement activation upon antigen recognition 24,30,31 . These exciting advances in unveiling distinctive molecular events of Abs reveal its compelling implications in resolving heterogeneous conformations of Ab-Ag complexes.…”
mentioning
confidence: 99%
“…As the affinity of C1q for a single IgG is very weak 20,21 , avidity achieved through simultaneous binding of all six globular domains to six oligomerized IgG molecules is paramount for a strong response 15,[17][18][19] . Furthermore, it was found that IgG hexamerization could be manipulated by specific point mutations in the Fc-Fc contact region that enhance such oligomerization 15,18,22 . While these hexamer-enhancing mutations in IgG potentiate the efficacy of MAC-dependent cytotoxicity on tumor cells and Gram-negative bacteria 15,23 , their effect on complement-dependent phagocytosis is not known.…”
Section: Introductionmentioning
confidence: 99%